Natural resin acid –enriched composition as a modulator of intestinal microbiota and performance enhancer in broiler chicken. (4th March 2015) - Kettunen, H.; Vuorenmaa, J.; Rinttilä, T.; Grönberg, H.; Valkonen, E.; Apajalahti, J.
Summary: Resin acids extracted from coniferous trees are known for their antimicrobial and antifungal effects. This trial investigated the effect of a natural resin acid-enriched composition (RAC) on the gastrointestinal microbiota and productive performance of broiler chicken. The results demonstrated that at or above 5 mg/l, RAC prevented the growth of a pure culture of Clostridium perfringens, a causative agent of necrotic enteritis in poultry. Next, the effects of RAC on the microbial community were studied in a fermentation model with both the microbial inoculum and substrate for the microbes isolated from the ileum of broiler chickens. RAC was included at 0, 0.1 and 1 g/kg digesta, and supplementation decreased the relative proportion of lactic acid and increased that of acetic acid produced during the fermentation in a dose-dependent manner. At 1 g/kg inclusion, RAC decreased the density of lactobacilli. The final part of the experiment investigated the influence of RAC on the performance and intestinal microbiota of necrotic enteritis (NE)-challenged broiler chickens. A wheat and soy -based diet was supplemented with RAC at 0, 0.5, 1 and 3 g/kg. The chickens were challenged with Eimeria maxima oocysts on day 11, and a pure culture of C. perfringens on day 14. On day 17, the final day of the trial, RAC inclusion at 1 and 3 g/kg of feed significantly increased body weight. At 3 g/kg RAC numerically decreased the daily mortality seen during the challenge period. In the ileum, RAC at 1 g/kg reduced the NE-associated peak of microbial lactic acid production. Overall, the data suggested that the dietary ingredient RAC has the potential to act as a performance-enhancer and microbial modulator in broiler chickens.